Cartes des goûts, cartes du monde - Clarisse Didelon (Confins)
Food is in relation with the natural environment, but also with culture. In a world perspective, the cartography of the production of foodstuffs (grains, meats, tropical goods, alcoholic drinks) and of their consumption allows to highlight certain phenomena that play a role in the globalization, for example, the tension between cultural convergence and local particularities claims, but also the relations between northern and southern countries.